2017
DOI: 10.1002/bio.3408
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of carbon‐based quantum dots from starch extracts: Optical investigations

Abstract: Carbon-based quantum dots (C-QDs) were synthesized through microwave-assisted carbonization of an aqueous starch suspension mediated by sulphuric and phosphoric acids. The as-prepared C-QDs showed blue, green and yellow luminescence without the addition of any surface-passivating agent. The C-QDs were further analyzed by UV-vis spectroscopy to measure the optical response of the organic compound. The energy gaps revealed narrow sizing of C-QDs in the semiconductor range. The optical refractive index and dielec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 45 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…Although they can generally follow either top-down or bottom-up routines, 1,[38][39][40][41] bottom-up approaches attract increasing interest, due to the versatility of potential carbon precursors and to the possibility to modify CDs chemical composition by using heteroatom-containing doping agents. A variety of commercial and natural precursors were already tried, like starch, 3,42 gelatin, 43 grass, 44,45 banana and orange juices, 46 bread, 47 chocolate, 8 meat, 48 soy milk, 49 instant coffee, 17 black tea, 50 beer, 51,52 and egg white. 53 While such attempts are a priori interesting, the natural materials suffer from their heterogeneity, unknown impurities, and oen unknown chemical composition that is strongly affected by uncontrolled factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although they can generally follow either top-down or bottom-up routines, 1,[38][39][40][41] bottom-up approaches attract increasing interest, due to the versatility of potential carbon precursors and to the possibility to modify CDs chemical composition by using heteroatom-containing doping agents. A variety of commercial and natural precursors were already tried, like starch, 3,42 gelatin, 43 grass, 44,45 banana and orange juices, 46 bread, 47 chocolate, 8 meat, 48 soy milk, 49 instant coffee, 17 black tea, 50 beer, 51,52 and egg white. 53 While such attempts are a priori interesting, the natural materials suffer from their heterogeneity, unknown impurities, and oen unknown chemical composition that is strongly affected by uncontrolled factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…UV–Vis spectra of CQD are shown in Fig. S3, energy bandgap ( Eg ) can be calculated by the formula [18] E=h)(c/λ where E is energy bandgap, h is Planck's constant, c is speed of light and λ is a cut‐off wavelength. Based on the UV–vis spectra of CQDs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has reported that the CQDs can be used as cellular imaging [17], in order to determine that, we chose MitoTracker Red CMXRos (50 nM), a commercially available mitochondrial fluorescent probe to show red colour under imaging [18], as shown in Fig. 6 a , the obtained images clearly visualise the phase image of Hela cells, major mitochondria stained red with CMXRos under 633 nm excitation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon nanomaterials have been extensively studied due to their low toxicity and good stability . Particularly, carbon dots (C‐dots) have tuneable excitation and emission fluorescence properties, as well as excellent biocompatibility, and have been widely used as fluorescence probes for different target analytes such as metal ions, anticancer drugs, organophosphorus pesticides, and enzymes …”
Section: Introductionmentioning
confidence: 99%